Natural products in the treatment of diabetic foot infection - Mohsen Nazari; Leili Shokoohizadeh; Mohammad Taheri (European Journal of Medical Research)
Abstract Diabetic foot infections (DFIs) are a significant complication in diabetes mellitus, leading to increased morbidity, hospitalizations, and healthcare burdens. The growing prevalence of antibiotic-resistant pathogens has reduced the efficacy of conventional treatments, highlighting the need for alternative therapeutic strategies. Natural products, known for their antimicrobial, anti-inflammatory, and wound-healing properties, have garnered attention as potential treatments for DFIs. This review examines key natural compounds, including eugenol, thymol, carvacrol, curcumin, and Aloe vera, and their mechanisms of action in combating diabetic infections. We analyze the antimicrobial efficacy of these compounds, their ability to inhibit biofilm formation, and their role in wound healing. The review also explores challenges in integrating natural products into clinical practice and the potential for their use alongside or in place of traditional antibiotic therapies. Our findings suggest that natural products could play a crucial role in developing sustainable and effective treatment strategies for DFIs, especially in the face of rising antimicrobial resistance.